The anti-malarial atovaquone increases radiosensitivity by alleviating tumour hypoxia - Ashton, Thomas M.; Fokas, Emmanouil; Kunz-Schughart, Leoni A.; Folkes, Lisa K.; Anbalagan, Selvakumar; Huether, Melanie; Kelly, Catherine J.; Pirovano, Giacomo; Buffa, Francesca M.; Hammond, Ester M.; Stratford, Michael; Muschel, Ruth J.; et al. (Nature communications, 2016)
Tumour hypoxia renders cancer cells resistant to cancer therapy, resulting in markedly worse clinical outcomes. To find clinical candidate compounds that reduce hypoxia in tumours, we conduct a high-throughput screen for oxygen consumption rate (OCR) reduction and identify a number of drugs with this property. For this study we focus on the anti-malarial, atovaquone. Atovaquone rapidly decreases the OCR by more than 80% in a wide range of cancer cell lines at pharmacological concentrations. In addition, atovaquone eradicates hypoxia in FaDu, HCT116 and H1299 spheroids. Similarly, it reduces hypoxia in FaDu and HCT116 xenografts in nude mice, and causes a significant tumour growth delay when combined with radiation. Atovaquone is a ubiquinone analogue, and decreases the OCR by inhibiting mitochondrial complex III. We are now undertaking clinical studies to assess whether atovaquone reduces tumour hypoxia in patients, thereby increasing the efficacy of radiotherapy. Tumour hypoxia reduces the efficacy of radiotherapy. Starting from a drug screen, here the authors demonstrate that the anti-malarial, atovaquone, reduces the oxygen consumption rate of cancer cells by inhibition of mitochondrial complex III and sensitises to radiotherapy by reducing tumour hypoxia.